1997
DOI: 10.1002/jmri.1880070136
|View full text |Cite
|
Sign up to set email alerts
|

Dual dynamic contrast‐enhanced MR imaging

Abstract: A method was devised for obtaining dynamic contrast-enhanced T1-weighted and relaxation rate (delta R2*) images simultaneously to evaluate regional hemodynamics of the brain tumors. On a 1.5-T MR system, dual dynamic contrast-enhanced images were obtained using a gradient echo (dual echo fast field echo) pulse sequence with the keyhole technique to improve temporal and spatial resolution during a rapid bolus injection of gadopentetate dimeglumine. The dynamic T1 contrast images were obtained from the first ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 34 publications
0
51
0
Order By: Relevance
“…It has been suggested that the effects of extravasation can be minimized with the application of a preloading dose of contrast agent 3 or by using multiecho methods. 4,5 More complex modeling has been undertaken to parse out the separate effects of permeability, and some of these methods are discussed in the section on permeability imaging.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the effects of extravasation can be minimized with the application of a preloading dose of contrast agent 3 or by using multiecho methods. 4,5 More complex modeling has been undertaken to parse out the separate effects of permeability, and some of these methods are discussed in the section on permeability imaging.…”
Section: )mentioning
confidence: 99%
“…For the T1 criteria to be satisfied, they suggested that the sequences should be made less T1-sensitive by lowering the flip angles (to 30°rather than 90°), though this results in decreased SNR; another approach would be to directly measure and correct by using multiple echoes. 4 Recalling Eq 20 and explicitly including plasma contributions to tissue concentration yields the following equation:…”
Section: )mentioning
confidence: 99%
“…Although it has not been explicitly shown here, DC-EPIK offers a degree of flexibility in that the SPARSE factor, the keyhole factor and the oversampling factor are adjustable parameters which influence the temporal resolution and the achievable degree of immunity from susceptibility artefacts. Because DC-EPIK intrinsically acquires two images, registration of these images is inherent; this is, of course, applicable to other dual echo sequences (Barbier et al 1999, Miyati et al 1997, Vonken et al 2000 also, but DC-EPIK is faster since it is based on EPI rather than FLASH. The acquisition of an independent keyhole during each shot ensures that the contrast-to-noise of each reconstructed image is, to all practical intents, an independent measure.…”
Section: Discussionmentioning
confidence: 99%
“…Most of this work focused on the problem of obtaining accurate tumor perfusion measurements in the presence of extravascular contrast agent leakage in regions of disrupted blood-brain barrier (12)(13)(14). Vonken and coworkers (15) also recognized the need to eliminate T 1 effects in order to obtain accurate brain perfusion estimations using the ECF agent GdDTPA, but there was no discussion in that work on the relative magnitude and sequence dependence of the T 1 effect.…”
Section: Discussionmentioning
confidence: 99%